Combining a geographic information system, known dietary, foraging and habitat preferences, and stable isotope analysis to infer the diet of Magellanic Penguins in their austral distribution - Ciancio Blanc, Javier Ernesto (2016)
The Magellanic Penguin (Spheniscus magellanicus) is the most abundant and widely distributed top marine predator of Atlantic Ocean waters off the Patagonian coast. During the breeding season, this species consumes thousands of tonnes of its prey and has a significant effect on populations of fish and squid near the Penguin's breeding colonies. We combined data on stomach contents, known habitat preferences of their prey, stable isotope analysis and a geographic information system to describe the diet of Magellanic Penguins in their austral distribution. On this basis, we present a comprehensive analysis of the trophic ecology of the species, the diet of which is poorly known (only a few analyses of stomach contents). Stable isotopes revealed a mean trophic level of 5.3 (range 4.5-5.8) and a diet in accordance with spatio-temporal overlap analysis. This study shows that Magellanic Penguins forage on few prey species not targeted by commercial fisheries in this region, mostly Patagonian Sprat and Longfin Squid. Moreover, we demonstrated that a combination of complementary tools can be used to describe the trophic relationships of wide-ranging marine predators, such as seabirds.